Semiotika Michael Riffaterre Dalam Puisi Fî ‘Ainika Unwanî Karya Faruq Juwaidah - Fatimatuz Zahro (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
This study aims to analyze the structure and meaning of the poetry text fii ainika unwanii using Riffatere's semiotic theory. Methods of This research uses a qualitative method and Riffaterre's semiotic approach. This study describes the reading of heuristics, hermeneutics and described by matrices, models, variants and hypograms in fii ainika unwani poetry. This type of research uses qualitative, data in the form of stanzas or lines in the poem fii ainika unwani by Faruq Juwaidah. The data source is a poetry text consisting of 2 stanzas and 32 lines. While the presentation of the data is done by drawing conclusions by describing the results of the application of Riffatere's semiotic theory in the form of words, sentences and paragraphs in a systematic, factual and accurate manner, semantic validity is done by reading and repeating poetry and the results that are relevant to the theory. The results show that the heuristic reading in the form of translation of the meaning is generally described about love. love, love, fear of loss and hope. The variant of the poem that is emphasized is in the first stanza which includes the essence, namely: he said, you will forget me. And the variant in the thirteenth stanza that answers questions and hopes in the first stanza is